Avaliação da atividade antimicrobiana dos extratos de Hamamelis virginiana L. - Serafim, Valeska Farias (2016)
Several plants have antimicrobial effects, which may represent an alternative therapy for various infectious diseases. The objective was to evaluate the in vitro antibacterial activity of glycolic extracts of propolis and Hamamelis virginiana L. against strains patterns of Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922). The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined by broth microdilution tests on Müller Hinton broth, and the drugs prepared in dimethylsulfoxide (DMSO) and standardized inoculum to be 0.5 of the McFarland scale (106 CFU / ml). The Minimum Inhibitory Concentrations and Minimum Bactericidal Concentrations Hamamelis virginiana L. extract were respectively for S. aureus 100 ug / ml and 200 ug / ml and E. coli 200 ug / ml and 250 ug / ml. In the tested experimental conditions, the extracts showed antibacterial activity against the strains S. aureus and E. coli.